Impact of ESG Scores and ESG Controversies on Firm Value in Southeast Asia (2018-2022), Moderated by Family Ownership Influence - Wahyudi Safitryanto; Cynthia A Utama (Green Publisher Indonesia, 2026)
The notion of Environmental, Social, and Governance (ESG) has become increasingly significant in global corporate strategies, particularly in addressing sustainability and climate change issues. This study analyzes the impact of differences between ESG scores and ESG controversies on Firm Value in publicly traded firms across Southeast Asia between 2018 and 2022, and family ownership serving as a moderating variable. This study provided a different perspective from previous research, which measured the difference between ESG Scores and ESG Controversies using ESG True Value and ESG Combined. The analysis used two regression models: Ordinary Least Squares (OLS) and Random Effects Model (REM). The results of this research showed that true value data tested using OLS and ESG Combined data using the REM model, the difference between ESG Score and ESG Controversies was proven to adversely impact corporate value. The adverse effect was determined to be stronger in family enterprises. This significant negative effect on family firms was influenced by factors including firm orientation, internal information dissemination in family firms, and their ESG disclosures.